2009
DOI: 10.1590/s1808-18512009000300005
|View full text |Cite
|
Sign up to set email alerts
|

Lesão medular no Centro de Reabilitação e Readaptação Dr. Henrique Santillo (CRER- GO)

Abstract: OBJETIVO: avaliação epidemiológica de pacientes com diagnóstico de lesão medular internados para reabilitação na enfermaria do Centro de Reabilitação e Readaptação Dr. Henrique Santillo (CRER) em Goiânia, Goiás. MÉTODOS: estudo epidemiológico retrospectivo baseado na coleta de dados dos prontuários médicos dos pacientes internados no período de Março de 2007 a Março de 2009. RESULTADOS: foram avaliados 208 pacientes, com predomínio do sexo masculino (78,85%) e idade média de 35,3 anos. O déficit neurológico ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
14

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 3 publications
(5 reference statements)
3
11
0
14
Order By: Relevance
“…These data can be directly related to the fact that the women are carrying more vehicles (motorcycles, cars), as well as being professionally more inserted in civilian buildings, where falls are more frequent. In relation to age, this survey shows that it ranged from eight to 72 years, mean 33.9 ± 13.5 years, in line with other studies 10,12,15,16 .…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These data can be directly related to the fact that the women are carrying more vehicles (motorcycles, cars), as well as being professionally more inserted in civilian buildings, where falls are more frequent. In relation to age, this survey shows that it ranged from eight to 72 years, mean 33.9 ± 13.5 years, in line with other studies 10,12,15,16 .…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 92%
“…Other works point to the same results 12,15,20 . In Santo André city, São Paulo State 8 , however, a study of 100 patients between 2003 and 2006 observed reversal of this pattern, with prevalence of the cervical, lumbar and thoracic segments, respectively.…”
Section: Discussion Discussion Discussion Discussion Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The main causes of SCI shown in the present study were traffic accidents, followed by gunshot wounds. Conceição et al 20 and Custódio et al 21 demonstrated similar results, with the same variables as the main causes. Different data were found by Brito et al 23 that reported falls (42.6%) as the main cause.…”
Section: 33mentioning
confidence: 65%
“…36 The ejaculation -exit of the seminal liquid through the urethra to the external environment -has its command located in the S2-S3-S4 segments, and depends not only on the integrity of the 17,18,19 and the prevalence of paraplegia and complete injuries. 8,20,21 Conversely, Dahlberg et al 22 showed quadriplegia (51%) and incomplete injuries (52%) as being the majority, after interviewing 92 patients. The main causes of SCI shown in the present study were traffic accidents, followed by gunshot wounds.…”
Section: 33mentioning
confidence: 98%